Suppression of ferromagnetic correlations in hole-doped SrCo2As2 - M Morena; A Van Der Spuy; Y Liu; R Warmbier; Abhishek Pandey (JPhys Materials)
We report the growth of high-quality single crystals of hole-doped composition ${Sr_{0.95}K_{0.05}Co_2As_2}$ and present an investigation of its structural, electronic, thermal, and magnetic properties. Our results show that hole doping leads to a substantial suppression of ferromagnetic (FM) correlations present in ${SrCo_2As_2}$ leading to nearly isotropic magnetic susceptibilities $χ_{ab,c}(T)$ of ${Sr_{0.95}K_{0.05}Co_2As_2}$ . The presence of FM fluctuations is considered one of the detrimental reasons why ${SrCo_2As_2}$ does not achieve a superconducting ground state despite having a precursor for it in the form of stripe-like antiferromagnetic fluctuations. The suppression of FM fluctuations leads to qualitative similarities between the properties of hole-doped ${SrCo_2As_2}$ and the end member of superconducting 122 iron-arsenide family KFe _2 As _2 . Our results also infer the presence of strongly correlated electronic states in ${Sr_{0.95}K_{0.05}Co_2As_2}$ . Further, they show that the electronic structure of ${SrCo_2As_2}$ as well as this hole-doped composition is exceptionally unstable in the vicinity of Fermi level $E_{F}$ for small alterations in the structural parameters and sensitively depends upon the details of simulation.